Rear Wheel Drive Sprocket Gear Transmission Design for Electric car - Tohasan, Achmad; Prihastuty, Endang; Yudisworo, W. Djoko (Mestro: Jurnal Teknik Mesin dan Elektro, 2024)
Electric vehicle engines are the same as vehicles with combustion motors, namely they are an assembly of several mechanisms consisting of three main parts, namely the drive, the power transmission system and the driven part. The electric car used for this research is a conversion of a petrol car, where the drive uses a 3 KW BLDC electric motor. The BLDC motor shaft power is transmitted to the axle pinion shaft using a sprocket gear transmission. So an analysis of the sprocket gear design, both ratio, size (type), strength and age of the sprocket gear to be used needs to be carried out. The initial step is to calculate the design power by looking at the correction factors in the table for the type of electric motor drive, then determining the chain number on the graph by first calculating the torque moment. The linear speed of the chain that occurs is influenced by the size of the gears and the input rotation of the electric motor, the greater the speed, the smaller the torque, so the gear ratio needs to be considered in determining the maximum linear speed. After knowing the chain plan number, it can be tested by calculating whether the chain number technically meets good security or not. In this research, the sprocket chain design, namely chain roller number 40 with a maximum load of 33.74 kg, is good, namely greater than sf = 6.